Quantitative lung T cell responses aid the rapid diagnosis of pulmonary tuberculosis - Dheda, K; van Zyl-Smit, R N; Meldau, R; Meldau, S; Symons, G; Khalfey, H; Govender, N; Rosu, V; Sechi, L A; Maredza, A; Semple, P; Whitelaw, A; et al. (Thorax, 2009)
Background:The diagnosis of smear-negative pulmonary tuberculosis (TB) is problematic. There are limited data on the profile of alveolar TB antigen-specific T cells, and their utility for the rapid immunodiagnosis of pulmonary TB is unclear.Methods:Antigen-specific interferon γ (IFNγ) responses to the RD-1 antigens ESAT-6 and CFP-10 (T-SPOT.TB and QuantiFERON-TB-Gold-In-Tube), heparin-binding haemagglutinin and purified protein derivative were evaluated, using alveolar lavage cells, in 91 consecutively recruited South African patients suspected of having TB.Results:Of 85 evaluable patients (29% HIV+), 24, 11, 48 and 2 had definite TB, probable TB, non-TB and an uncertain diagnosis, respectively. Between 34% (T-SPOT.TB) and 41% (QuantiFERON-TB-Gold-In-Tube) of all test results were inconclusive. Failure of the positive control was significantly higher with the QuantiFERON-TB-Gold-In-Tube than with T-SPOT.TB (85% vs 46% of inconclusive results; p = 0.001). Using staphylococcal enterotoxin B, compared with phytohaemagglutinin, substantially reduced failure of the positive control (25% to 3%; p = 0.02). In evaluable samples, when the definite and non-TB groups were used for outcome analysis, the percentage sensitivity, specificity, positive predictive value and negative predictive value for T-SPOT.TB (⩾20 spots/million alveolar mononuclear cells) and QuantiFERON-TB-Gold-In-Tube (0.35 IU/ml) were 89, 94, 89 and 94% (n = 55) and 55, 86, 77 and 69% (n = 46), respectively. Rapid diagnosis of TB was achieved more frequently with T-SPOT.TB than with smear microscopy (14/24 (58%) vs. 7/24 (29%) of definite TB cases; p = 0.02). Heparin-binding haemagluttinin and purified protein derivative alveolar lymphocyte IFNγ responses had poor performance outcomes.Conclusion:Provided evaluable results are obtained, the RD-1, but not the heparin-binding haemagglutinin or purified protein derivative, alveolar lymphocyte IFNγ ELISPOT response is a useful rapid immunodiagnostic test for TB. However, test utility in high-burden settings may be limited by the high proportion of inconclusive results.